Haptic systems architecture modeling - Weber, Anton (Springer Vienna, 2012)
The present work showcases a novel approach to modeling systems architectures by utilizing Lego bricks and RFID technology. The presented solution can be used by systems and software architects to communicate their design decisions with other stakeholders in the developments process such as customers and managers involved. The software provided in this book helps to get a concrete tool showing how the approach can be applied. If the reader is interested in experimenting with this approach, they will need to purchase LEGO © blocks and the required RFID technology needed for this.